1997
DOI: 10.1007/978-94-011-4896-2_60
|View full text |Cite
|
Sign up to set email alerts
|

Reduced and zero-tillage options for establishment of wheat after rice in South Asia

Abstract: One of the major constraints to higher production of wheat on the 12 million hectares of rice-wheat grown in the Indo-Gangetic flood plains of South Asia is late planting and resultant poor plant stands. Late planting results in a linear decline in yield potential equivalent to 1-1.5% loss ha-1 d-I when planting occurs after November. Late harvest of the previous rice crop or long turnaround time from rice harvest to wheat planting are two major causes of late wheat planting. Reduced or zero-tillage options ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 4 publications
2
30
0
1
Order By: Relevance
“…Research had shown that wheat yield was reduced by 1-1.5% for each day that seeding was delayed after November 30 (Hobbs et al, 1997). After the harvest of the rice crop, tillage required several days, delaying the date of seeding of the wheat.…”
Section: Timeliness Of Seedingmentioning
confidence: 99%
“…Research had shown that wheat yield was reduced by 1-1.5% for each day that seeding was delayed after November 30 (Hobbs et al, 1997). After the harvest of the rice crop, tillage required several days, delaying the date of seeding of the wheat.…”
Section: Timeliness Of Seedingmentioning
confidence: 99%
“…2005, Sharma et al. 2007a), a frequent circumstance as late‐maturing rice cultivars used in rice‐wheat cropping systems push back the sowing of wheat (Hobbs and Giri 1997). Yields of late‐seeded wheat are reduced by as much as 40% (de Lespinay 2004, Sharma and Duveiller 2004, Duveiller et al.…”
mentioning
confidence: 99%
“…Rickman et al (1999) reported that crop lodging is a significant problem in dry seeded rice in Cambodia, particularly with traditional varieties with full conventional tillage systems but machine drilling of seeds could reduce lodging to less than 10%. Chinese scientists have developed a two-wheel tractor operated seeder that provides tillage, seeding and leveling in one operation (Hobbs et al, 1997). The main components were shallow rotovator, six-row seeding system and soil compaction roller.…”
Section: The Agriculturists 11(2): 87-95 (2013) Issn 2304-7321 (Onlinmentioning
confidence: 99%